EDUKASI PETERNAK TENTANG PEMILIHAN BIBIT DOMBA DI KECAMATAN SAMARINDA UTARA KOTA SAMARINDA - Fanani, Anhar Faisal; Ismanto, Arif; Anindyasari, Dinar; Indana, Khoiru; Simanjuntak, Servis; Anjani, Fandini Meilia; Ardiansyah, Ardiansyah; Wibowo, Ari; Rizkuna, Akhmat; Fajrih H, Nurul (Universitas Mataram, 2025)
Livestock performance is influenced by genetics, the environment, and their interactions. The livestock commonly raised by the community are small ruminants, particularly sheep. Therefore, it is important to provide knowledge and information regarding sheep breeding stock selection. This activity was also based on regional regulations concerning sheep farming in East Kalimantan. The purpose of this program was to educate farmers in North Samarinda District on selecting quality breeding stock, thereby improving their understanding and awareness of good breeding practices. The community service activity (PKM) was conducted at the Community Hall of Lempake Subdistrict, North Samarinda District, Samarinda City. The implementation methods included introductions and opening, delivery of educational materials, and discussion through a question-and-answer session. Through this educational activity, it is expected that farmers will gain better awareness of the importance of breeding stock selection, adapt improved management practices after socialization and training, and increase active involvement from the farming community. Farmers in North Samarinda District became more aware of the importance of breeding stock selection based on SNI (Indonesian National Standard) criteria after attending the educational program at the Lempake Community Hall. Farmers also demonstrated positive behavioral changes in selecting sheep using SNI standards. The impact of education was reflected in improved health, body size, and qualitative traits of sheep, resulting in better performance. In addition, this activity received strong support from farmer associations and related institutions in applying breeding stock selection practices. Conclusion: To improve productivity, proper breeding stock selection and management, along with the application of supporting technologies, are necessary. Thus, sheep farming has the potential to become an important source of household income and help farmers expand their sheep farming businesses.